Sistem Informasi Peminjaman Buku di Perpustakaan Berbasis Web pada Suku Dinas Perspustakaan dan Kearsipan Kota Administrasi Jakarta Barat - Suci Hesti Prastika; Muhammad Cordiaz (CV. Multi Kreasi Media, 2022)
The year 2020 is a year of global disaster for humanity. The year 2020 begins with a viral disaster that attacks humanity with very fast and fatal disease transmission. This virus is called the Corona virus (Covid19). Covid-19 forces people to keep their distance from each other so that the transmission process does not occur too quickly. As a result, many human activities stop functioning, such as the economy, congregational worship, transportation, education, and others. From several public library sites or universities in several countries, there is no indication that their libraries are always open to offer loan and return services. With these problems the author proposes a web-based book lending information system using the XP (Extreme Programmig) method. This web-based library book lending system is very much needed at the West Jakarta City Administration of Library and Archives Sub-department. From this system, it is hoped that it will make it easier for people who want to borrow books from the library. The result of this research is a web-based book lending system in a library. Previously, people had to come to the library first to find the book they wanted, then register their loan with the librarian, then with this system, people only need to open it on the web, and look for a list of the desired books and register them online. It is hoped that with this information system, it can be useful for the wider community. In this information system, the public can schedule arrivals to the library, so that there is no accumulation of visitors in the library.